Tapioca Waste-Methyl Methacrylate Irradiation for Biodegradable Plastic Raw Materials - Akhmad Rasyid Syahputra; Tita Puspitasari; Santoso Prayitno; Ade Lestari Yunus (Research Center for Chemistry - LIPI, 2020)
Nuclear technology can be applied not only as an energy (electricity) but also in industry as as an initiator on polymer reaction. Tapioca waste is used due to its biodegradability properties. Tapioca waste gel is formed by adding equal aquades ratio to waste weight. After gel formed, several concentrations of methyl methacrylate (w/w) is added to the gel then packed into 150 mL ampule. Using Co-60 gamma irradiation source, gel is irradiated at 5 kGy absorbed dose. Gel is extracted using acetone to get rid of sample from impurities. Glycerol as a plasticizer is added to the gel to increase polymer flexibility. Gel-Glycerol mixing is done at 60ÂºC, 250 rpm for one hour by adding aquadest. To analyze mechanical properties, firstly, we need to mold samples using pressurized-hot press machine. Film is formed to type 5 specimen (dog bone, astm d638-14). Specimen is tested by analyzing tensile strength characteristics. Fabrication of biodegradable plastic based packaging by using starch has an increasement of mechanical and thermal properties at 5 kGy absorbed dose. Methyl methacrylate 25, 50, 75, 100, 125 and 150% addition to the solution has 10-24 MPa tensile strength. Gel fraction has range between 88-100%. Even the lowest ratio of monomer addition can provide highest gel fraction to improve mechanical properties of tapioca waste.Â